A Novel Method for Adding Graphite Flakes to Al2O3–ZrO2‐Graphite Composites and Performance Testing. Issue 7 (2nd April 2019) - Huang, Yong; Ai, Yunlong; Chen, Weihua; He, Wen; Zhang, Jianjun; Liang, Bingliang
Abstract : A novel method to produce graphite flakes was invented, and this method is good for homogeneous of graphite among the Al2 O3 ‐ZrO2 ‐Graphite composite powder. Graphite ball, alumina ball, and alumina powder are put into planetary muller together, and the graphite flakes are produced by shear forces between the surface of graphite and alumina ball during the ball mill process. Al2 O3 ‐χwt%ZrO2 ‐3wt%Graphite (A‐χZ‐3Gr, χ = 5, 10, 15, 20) composites powder are developed by this new method and then are sintered using microwave at a temperature of 1500 °C for 30 min in argon atmosphere. Actually 3wt%Graphite (Gr) is fully capable of forming a lubricating film on the rubbing surface of A‐χZ‐3Gr composites to ensure a low friction coefficient. On the other hand, the ZrO2 addition is good for the mechanical properties. The effect of ZrO2 addition on the relative density, hardness, fracture toughness and bending strength of the various A‐χZ‐3Gr composites are investigated. The performance of A‐χZ‐3Gr composites has been greatly improved as compared with Al2 O3 ‐3 wt% Graphite sintered under the same condition. The A‐10Z‐3Gr composite exhibited excellent performance such as its relative density, hardness, fracture toughness, bending strength, friction coefficient, and wear rate are 95.4%, 323.7Mpa, 5.8Mpa · m 1/2, 9.3Gpa, 0.31 and 5.19 × 10 −6 mm 3  Nm −1, respectively. Abstract : This article introduces a new way to add graphite flakes on Al2 O3 /ZrO2 ceramics matrix, which has achieved fine results through tests and analyses. The mechanical and tribological properties show the regularity of A‐χZ‐3Gr composites. Moreover, ZrO2 particles play a important role as an toughening and reinforcing agent, which effectively increases the properties of A‐χZ‐3Gr composites.